New approaches to teaching folk and fairy tales - Schwabe, Claudia (Claudia Mareike Katrin); Jones, Christa (Utah State University Press, 2016)
"Invaluable hands-on materials and pedagogical tools from an international group of scholars who share their experience in folk and fairy-tale texts and films in a wide range of academic settings. Groundbreaking scholarly perspectives on how to teach fairy tales in a variety of courses and disciplines "--Provided by publisher